Influence of Microbiota on Intestinal Immune System in Ulcerative Colitis and Its Intervention - Zhang, Sai-Long; Wang, Shu-Na; Miao, Chao-Yu (Frontiers in Immunology, 2017)
Ulcerative colitis (UC) is an inflammatory bowel disease with chronic and recurrent characteristics caused by multiple reasons. Although the pathogenic factors have not been clarified yet, recent studies have demonstrated that intestinal microbiota plays an major role in UC, especially in the immune system. This review focuses on the description of several major microbiota communities that affect UC and their interactions with the host. In this review, eight kinds of microbiota which are highly related to IBD, including Faecalibacterium prausnitziib, Clostridium clusters IV and XIVa, Bacteroides, Roseburia species, Eubacterium rectale, Escherichia coli, Fusobacterium and Candida albicans are demonstrated on the changes in amount and roles in the onset and progression of IBD. In addition, potential therapeutic targets for UC involved in the regulation of microbiota, including NLRPs, VDR as well as secreted proteins, are discussed in this review.